The breakthrough potential of LA-ICP-MS for understanding the chemical stratigraphy in deep polar ice cores - Pascal Bohleber; Remi Dallmayr; Martin Rittner; Marco Roman; Nicolas Stoll; Frank Wilhelms and Carlo Barbante (University of Bern, 2022)
State-of-the-art ice core research calls for understanding the deepest and oldest ice sections at unprecedented resolution, not least for retrieving a 1.5 million-year “Oldest Ice Core” record from Antarctica. Mastering this frontier demands high-resolution analysis due to layer thinning and accounting for postdepositional changes to the stratigraphy. Its micron-scale resolution and micro-destructiveness make laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) especially suited for the analysis of chemical impurities in ice cores [1]. If employed for 2D imaging, LA-ICP-MS allows to map the spatial impurity distribution in ice. This already shows great potential for assessing the interplay of impurities and the ice matrix [2]. However, deep ice features ice crystals larger than a few cm and can alter the composition of its impurities by chemical reactions. To succeed further, LA-ICP-MS ice core analysis needs to cover a broad spectrum of elements while avoiding cutting ice cores into small-sized samples. Aiming to engage with the broad laser ablation community we present our latest developments and some initial steps in tackling this challenge. In a recently conducted pilot experiment we explored “time of flight” mass spectrometry for a range of elements, including Antarctic ice with very low concentrations [3]. Multielemental images at 20 microns resolution allow the geochemical characterization of impurities localized at crystal boundaries as well as clustered dust particles. Aiming to increase physical image dimensions and to avoid destructive sample preparation, we present first progress in developing a large cryocell housing up to 55 cm long ice core rods. Here, the main challenge is to expand on pioneering solutions [4] by integrating 2D imaging capabilities. When combined with a modern high-repetition rate laser system, a large imagingcapable cryocell would bring into reach the recording of centimeter or even decimeter-sized images along a broad range of analytes – ultimately making ...